2019
DOI: 10.1155/2019/1487013
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Autorefraction and Photorefraction with and without Cycloplegia Using 1% Tropicamide in Preschool Children

Abstract: Purpose. We aimed to investigate whether the accuracy of the Plusoptix A09 photorefractor in children with ametropia is enhanced by cycloplegia with 1% tropicamide. Methods. A total of 70 eyes (70 children) were retrospectively reviewed. Noncycloplegic photorefraction, cycloplegia with 1% tropicamide, cycloplegic photorefraction, and cycloplegic refraction with a tabletop autorefractometer were performed on all subjects in this order. Measurements were compared statistically. Results. The mean age was 45.9 ± 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…For the spherical component, this increase was 1.17D under cycloplegia. For the cylinder component, there was no difference in photorefraction with Plusoptix A09 [ 39 ]. Tuncer et al compared handheld Retinomax readings in children.…”
Section: Discussionmentioning
confidence: 99%
“…For the spherical component, this increase was 1.17D under cycloplegia. For the cylinder component, there was no difference in photorefraction with Plusoptix A09 [ 39 ]. Tuncer et al compared handheld Retinomax readings in children.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the autorefractometer used, the objective refraction measurements can be performed either with or without fogging, monocular or binocular, through the central or the whole pupil, and with or without open-field viewing. The results of objective refraction measurements vary among autorefractors, and those differences are in most cases clinically significant [ 6 , 7 , 8 ]. This could be explained due to the measurement principle and design of each.…”
Section: Introductionmentioning
confidence: 99%
“…Accuracy analysis of the cycloplegic measurements of both devices indicated that the cycloplegic measurements were more closely related to those of cycloplegic retinoscopy than the non-cycloplegic measurements, in terms of SE values. Although cycloplegic measurements with SureSight also yielded very close results, the cycloplegic measurements with Spot Vision were higher by about 0.25 D. Yilmaz Kiyak et al (9) found that cycloplegic measurements with the PlusOptix S04 (PlusOptix GmbH, Nuremberg, Germany), another photoscreener that uses the same principle, were higher by 1.06 D. Similarly, Yassa et al (26) reported that cycloplegic measurements with PlusOptix were higher by 0.78 D. Özdemir et al (27) found that photorefraction with cycloplegia led to overestimation of SE and spherical power. Schimitzek et al (17), on the other hand, reported that PlusOptix made cycloplegic measurements that were 0.12 D lower in an adult patient group (median age: 43 years).…”
Section: Discussionmentioning
confidence: 92%